Urban household travel behavior in a time of economic crisis: Changes in trip making and transit importance - Ulfarsson, Gudmundur F.; Steinbrenner, Anne; Valsson, Trausti; Kim, Sungyop (Journal of Transport Geography, 2015)
This research explores changes in trip frequency and importance of bus transit in an urban environment affected by the financial crisis of 2008. The survey was conducted in 2009 in the Reykjavik capital region of Iceland and yielded 1,160 responses. Descriptive analyses and multivariate statistics are applied. The results demonstrate the economic crisis influenced people's travel behavior. About 30% of the participants make fewer trips since the crisis, due in part to reduced income and/or unemployment, suggesting increased risk of transport-related social exclusion. About 20% of the participants perceive bus transit as more important than before, to some extent at the expense of personal automobiles. Important variables associated with reduced trip frequency and increased importance of bus transit were: working more at home and more than 40% household income reduction. Those using their own vehicle less also reported greater bus transit importance. The residents in the suburbs of Reykjavik and in the nearby communities were more likely than the residents in central parts of Reykjavik to reduce their number of trips, suggesting that central city residents were less sensitive to the economic crisis in terms of transportation. The importance of the bus system was found more based on personal and household characteristics than neighborhood type (urban, suburban, nearby communities).